Clinician-reported outcome measures in lupus trials: a problem worth solving. (August 2021) - Connelly, Kathryn; Golder, Vera; Kandane-Rathnayake, Rangi; Morand, Eric F
Summary: Systemic lupus erythematosus (SLE) remains a disease of high unmet clinical need. Because of substantial patient heterogeneity, the execution of clinical trials that successfully determine the efficacy of novel therapeutics compared with placebo is a continuous challenge. Clinician-reported outcome measures of treatment response used in SLE trials have evolved from the use of individual disease activity indices, including the SLE Disease Activity Index (SLEDAI) and British Isles Lupus Assessment Group (BILAG), to composite responder definitions such as the SLE Responder Index (SRI) and BILAG-Based Composite Lupus Assessment (BICLA), which are based on these indices. However, these approaches have notable drawbacks and defining the optimal clinical trial outcome measure for SLE remains a research goal. In this Viewpoint, we explore the strengths and limitations of existing indices and composite assessments, illustrating features which should be investigated in future analysis of trial data. Further, we provide a platform from which to advance new approaches to endpoint design, which is crucial to improve the interpretability and success of subsequent clinical trials in SLE.